ANALISIS JARINGAN IRIGASI BENDUNGAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA BERBASIS SPASIAL - Amalludin S. Kono; David P. Rumambi; Sandra Pakasi; Hildy Wulur (COCOS, 2014)
ABSTRACTSangkub dam was built in 2005, before the establishment of the regency of NorthBolaang Mongondow. This dam, with an approximate width of 100 meters, is planned toirrigate 3.601 ha of rice fields in two districts: Sangkub and Bintauna. In 2012, the damstarted operating and irrigated the rice fields in Sangkub. This research aims to provideinformation about the conditions of the irrigation network of Sangkub dam based on spatialanalysis. This research was conducted over the course of six months (August 2013 – January2014) in Sangkub dam, Sangkub district. Data was collected through surveys, image analysesand experiment using buoys. This research shows that Sangkub’s irrigation network does notmatch the planned schematics regarding number of buildings. There is a lack of floodgates inthe secondary channels in Tombolango and there are five overflow points and one leakagepoint in the irrigation channels of Sangkub dam.Keywords: Irrigation network, Sangkub dam, Spatial